Endoscopic third ventriculostomy in posterior fossa tumor - Ricardo Santos de Oliveira; Matheus Fernando Manzolli Ballestero (Brazilian Society for Pediatric Neurosurgery, 2020)
Posterior fossa (PF) tumors are among the most frequent primary neoplasms in children. Proximity to the fourth ventricle, and therefore cerebrospinal fluid (CSF) pathways, predisposes children with PF tumors to the development of obstructive hydrocephalus. Some patients with PF tumors require a permanent CSF diversion procedure prior to or after tumor removal. However, management of hydrocephalus in children with resectable PF tumors is still controversial. In order to minimize the use of permanent shunts and to avoid associated complications, some investigators have advocated routine preoperative application of endoscopic third ventriculostomy (ETV) only in selected patients. We showed a clinical video case who experienced a preoperatively ETV before the surgical resection of their posterior fossa tumor. The patient is a 5 year-old boy presented with progressive headaches, vomits and somnolence. Young children with severe preoperative hydrocephalus and a midline tumor should be considered at risk when preoperative treatment decisions are made. *de Oliveira RS and Ballestero MFM contributed equally to this manuscript